2021
DOI: 10.1101/2021.11.06.467345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent urinary tract infection and estrogen shape the taxonomic ecology and functional potential of the postmenopausal urobiome

Abstract: Community-acquired urinary tract infection (UTI) is among the most common bacterial infections observed in humans. Postmenopausal women are a rapidly growing and underserved demographic group who are severely affected by rUTI with a >50% recurrence rate. In this population, rUTI can persist for years, reducing quality of life and imposing a significant healthcare burden. rUTI is most often treated by long-term antibiotic therapy, but development of antibiotic resistance and allergy leave physicians with few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(192 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it is a limitation that 16S rRNA probes can only provide genus or familylevel identification and few genus-specific few probe sets have been validated in bladder tissue (42). Future studies should develop more probe sets that can identify other uropathogenic genera as well as genera that comprise the urinary microbiota (43,44). Once these new probe sets are developed, it will be important to determine the association between the genera information of bacteria embedded within the bladder and those identified in urine cultures from future UTI episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a limitation that 16S rRNA probes can only provide genus or familylevel identification and few genus-specific few probe sets have been validated in bladder tissue (42). Future studies should develop more probe sets that can identify other uropathogenic genera as well as genera that comprise the urinary microbiota (43,44). Once these new probe sets are developed, it will be important to determine the association between the genera information of bacteria embedded within the bladder and those identified in urine cultures from future UTI episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, L. crispatus has been previously associated with a healthy host urinary tract in some urinary microbiome studies (Pearce et al, 2014;Neugent et al, 2022) but no difference in abundance of this species was found in others (Komesu et al, 2020;Vaughan et al, 2021). Urinary L. crispatus isolates recently were found to inhibit E. coli CFT073 and E. faecalis in TSB medium via accumulation of phenyl-lactic acid (Abdul-Rahim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we conducted initial functional characterization of urinary lactobacilli from seven species under uniform conditions. Three of those species (eight strains) are from the abundant and frequently identified species in the female urinary tract: L. crispatus, L. gasseri and L. jensenii ( Ma et al., 2012 ; Komesu et al., 2020 ; Neugent et al., 2022 ). While lactobacilli inhabiting other ecological niches have been previously studied, urinary lactobacilli have not previously been characterized, despite their potential for direct interactions with uropathogens and potential clinical implications regarding urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation